Smart technology needs smarter management: Disentangling the dynamics of digitalism in the governance of shared solar energy in Australia - Hansen, Paula; Morrison, Greg; Zaman, Atiq; Liu, Xin (2020)
© 2019 Elsevier Ltd This article argues that the need for a better understanding of socio-technical interactions in shared renewable energy systems (SRESs) is exacerbated by the relevance of digital technologies to their governance. Addressing the question of how the use of digital technology affects system governance, this study applies the social-ecological system framework to a case study in Perth, Western Australia. The analysis finds that although the digital element enables the sharing of energy in the case study, it also increases the complexity of the social subsystem. While technology is often heralded as the solution, successful governance of digitally enabled SRESs may be more dependent on recognizing the importance and complexity of social interactions needed to manage the technology. The findings of the study are useful in developing and implementing appropriate governance mechanisms for SRESs in Australia and other parts of the world.